YAYASAN TRI BHAKTI DI PASTORAN KECAMATAN SIKAKAP KABUPATEN KEPULAUAN MENTAWAI (2002-2012) - Harefa, Kristofel; Zubir, Zusnelli; Nazmi, Ranti (Pendidikan Sejarah, 2013)
ABSTRACÂ Background history of the Foundation for the Tri Bhakti was originally intended to establish private educational institutions to be able to help people who can not afford education. The decision was taken based on stewardship policies implemented as a result of deliberation and consensus on the management of the institution implemented. The results of the stewardship agreement is also likely to determine the shape and range of activities that can be run at this educational institution. This thesis aims to describe the background of the establishment of the Foundation Tri Bhakti Foundation role in the Mentawai Islands District Sikakap in education and religion during the years 2002 to 2012.The results showed that the first, historical background of the establishment of the Foundation Tri Bhakti was originally intended to establish private educational institutions to be able to help people who can not afford education. The decision was taken based on stewardship policies implemented as a result of deliberation and consensus on the management of the institution implemented. The results of the stewardship agreement is also likely to determine the shape and range of activities that can be run at this educational institution. Second, the role of the Foundation in the field of education Tri Bhakti new limited formal education activities for junior high schools. However, Tri Bhakti Foundation has also helped organize non-formal education by opening English and computer courses. Furthermore the role of religion and religious foundations have been run properly, which for people who want to embrace a religion management is assisted by the foundation. As for the matter of religion, the foundation guiding young people through workshops to be able to understand the customs and culture, as well as several arts and cultural activities Mentawai tribe. Based on the research that has been done can be concluded that, Tri Bhakti Foundation has been carrying out its role in the District Sikakap in the field of formal education by setting up SMP, and non-formal with open courses in English and Computer. It also has roles in the field of religion by establishing cultural workshop to teach the younger generation the art of indigenous cultures Mentawai tribe.Keywords : Education, Religious, Tri Bhakti Foundation